2021
DOI: 10.34021/ve.2021.04.02(3)
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational and Economic Mechanism of Implementing the Concept of Green Logistics

Abstract: The article analyses the preconditions for shaping and developing the concept of a green economy. The stages of the evolutionary development of the circular economy are considered: work with waste; environmental performance strategies; maximum conservation in the era of resource depletion. Having analysed the scientific opinions on the emergence of “circular economy”, the paper has found out that this concept is identified with the terms “round economy”, “cyclical economy”, “recovery economy”, “closed-cycle ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 47 publications
(50 reference statements)
0
7
0
2
Order By: Relevance
“…As part of the digital transition to the development of the national economy, many normative acts have been adopted (Kwilinski et al, 2020;Rovňák et al, 2022) and comprehensive studies are being carried out (Vyshnevskyi et al, 2019;Orbik and Zozulakova, 2019;Vyshnevskyi et al, 2020;Albu and Albu, 2021;Kurniawan et al, 2022;Ma and Zhu, 2022;Ozturk and Ullah, 2022;Purnomo et al, 2022;Reza-Gharehbagh et al, 2022;Yang et al, 2022;Zhou et al, 2022;Orzeł and Wolniak, 2022;Brodny and Tutak, 2022;Mynenko and Lyulyov, 2022;Mańka-Szulik and Krawczyk, 2022; The situation is the same with the second trendthe transition to a green economy (European Commission, 2019;Kwilinski et al, 2019;Kuzior et al, 2019;Kuzior et al, 2021;Dźwigoł et al, 2021;Dzwigol et al, 2021;Astawa et al, 2021;Midor, 2022, Deja et al 2019. These questions are often examined simultaneously in many studies (Bonire and Gbenga-Ilori, 2021;Stoican and Chirieac, 2021;Li, Liu and Ni, 2021;Nham and Ha, 2022;Li and Wang, 2022;Zhang et al, 2022a;Zhang et al, 2022b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the digital transition to the development of the national economy, many normative acts have been adopted (Kwilinski et al, 2020;Rovňák et al, 2022) and comprehensive studies are being carried out (Vyshnevskyi et al, 2019;Orbik and Zozulakova, 2019;Vyshnevskyi et al, 2020;Albu and Albu, 2021;Kurniawan et al, 2022;Ma and Zhu, 2022;Ozturk and Ullah, 2022;Purnomo et al, 2022;Reza-Gharehbagh et al, 2022;Yang et al, 2022;Zhou et al, 2022;Orzeł and Wolniak, 2022;Brodny and Tutak, 2022;Mynenko and Lyulyov, 2022;Mańka-Szulik and Krawczyk, 2022; The situation is the same with the second trendthe transition to a green economy (European Commission, 2019;Kwilinski et al, 2019;Kuzior et al, 2019;Kuzior et al, 2021;Dźwigoł et al, 2021;Dzwigol et al, 2021;Astawa et al, 2021;Midor, 2022, Deja et al 2019. These questions are often examined simultaneously in many studies (Bonire and Gbenga-Ilori, 2021;Stoican and Chirieac, 2021;Li, Liu and Ni, 2021;Nham and Ha, 2022;Li and Wang, 2022;Zhang et al, 2022a;Zhang et al, 2022b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, there are high expectations about the positive impact of digitalization on achieving climate-neutral EU economy. However, there are alternative points of view on the positive impact of digitalization on the economic (Vyshnevskyi et al, 2020), social (Kwilinski et al, 2020) and environmental spheres (Shvakov and Petrova, 2019;Dźwigoł et al, 2021;Dzwigol et al, 2021). "The experience of the top 10 countries in terms of the level of digital competitiveness in 2019 has shown that digitalization does not contribute to the development of either a shared economy, or a "green" and circular economy, or an energy-efficient economy, and even hinders their development" (Shvakov and Petrova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…У дослідженнях сутності і природи економіки замкненого циклу найчастіше зустрічаються три домінантних принципи її існування та розвитку (3-R): 1R (reduce)економія ресурсів та пріоритет повторного використання сировини, матеріалів, продуктів; 2R (reuse) -максимально повне, ефективне та продуктивне використання товарів; 3R (Recycle) -відтворення побічної продукції та відходів для подальшого використання у виробництві [2]. Систематизація наукових підходів до трактування сутності циркулярної економіки дозволило науковцям визначити її зміст вітчизняними вченими як "…як інноваційний підхід до організації логістичних процесів, заснований на замкнутому русі ресурсів з їх мінімальними втратами у вигляді відходів і максимальному залученні вторинних ресурсів у виробництво з метою досягнення сталого розвитку логістичних систем" [3].…”
Section: виклад основного матеріалуunclassified
“…При цьому головним пріоритетом національної економіки визнано транскордонне співробітництво з Польщею з питань транспортної логістики у межах Транс'європейської транспортної мережі та модернізації транспортної інфраструктури на засадах кластеризації [1][2][3][4][5], цифровізації [6][7], екологізації [8][9][10][11][12][13] Питання міждержавного й транскордонного співробітництва у різних сферах економічної діяльності активно досліджуються зарубіжними й українськими науковцями.…”
Section: вступunclassified